2019
DOI: 10.3390/chemengineering3020040
|View full text |Cite
|
Sign up to set email alerts
|

Use of Calcined Dolomite as Chemical Precipitant in the Simultaneous Removal of Ammonium and Phosphate from Synthetic Wastewater and from Agricultural Sludge

Abstract: Phosphorus as phosphate and nitrogen as ammonium or nitrate are the main nutrients in wastewaters and agricultural sludges. They runoff easily to waterways and cause eutrophication in water bodies. However, ammonium and phosphate could be precipitated simultaneously and used as recycled nutrients. In this research, dolomite calcined at 650 °C, 750 °C, or 950 °C and commercial MgO were used as precipitants in simultaneous phosphate and ammonium removal from synthetic (NH4)2HPO4 solution and agricultural sludge.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…With FA (Mg:P:N = 1.6:1:1) and DOL based MgSO 4 solutions (Mg:P:N = 1.6:1:1 and 2:1:1), the removal percentages were 59%, 62%, and 63.5% respectively. In all cases, there was only a minor change in the removal percentages after 4 h. Pesonen et al [19] reported similar removal percentages calcined DOL. Myllymäki et al [17] reported nearly 100% ammonium removal but some of the ammonium was evaporated as ammonia gas due to high pH.…”
Section: Ammonium Removalmentioning
confidence: 59%
See 4 more Smart Citations
“…With FA (Mg:P:N = 1.6:1:1) and DOL based MgSO 4 solutions (Mg:P:N = 1.6:1:1 and 2:1:1), the removal percentages were 59%, 62%, and 63.5% respectively. In all cases, there was only a minor change in the removal percentages after 4 h. Pesonen et al [19] reported similar removal percentages calcined DOL. Myllymäki et al [17] reported nearly 100% ammonium removal but some of the ammonium was evaporated as ammonia gas due to high pH.…”
Section: Ammonium Removalmentioning
confidence: 59%
“…However, there was a clear drop in the removal percentage at the end of the experiments. Therefore, the lengths of the experiments were reduced to 4-6 h. Others found that when calcined, powdered DOL [19] was used as a precipitation agent after being dissolved to water, the contact time needed was at least 24 h. The same finding was made with FA in another study [17]. This is due to the low solubility of MgO to water.…”
Section: Ammonium Removalmentioning
confidence: 89%
See 3 more Smart Citations